Local government-academe partnerships touching and inspiring students in environmental monitoring - Oracion, Enrique G. (Silliman Journal, 2012)
In this paper, I describe the partnership between Bayawan City and Silliman University in the Philippines in monitoring the potential negative impact of the waste management center that the city has built to a nearby community. The city government provided the logistics while the Environmental Anthropology students did the survey for free. During the reflection sessions and in their written narratives, the students said that they were emotionally touched by the helpless conditions of households they interviewed. These household feared the potential negative effects of the said center, had no safe source of drinking water, and lived in a community with poor sanitation. This paper will show that service learning as a pedagogy will not only reinforce what students learn in the classroom but will also make them emphatic and inspired to use their skills to address a problem.